Molecular Genetic Testing in Pediatric and Adult Neurology in Iraq: New Experience and Challenges from a Developing Country - Saadi, Nebal Waill; Yassin, Batool Ali Ghalib; Makhseed, Nawal; Hadi, Ameer Shaker (Journal of Pediatric Neurology, 2020)
Inherited neurological disorders are reasonably common in pediatric and adult neurology practices. Genetic testing for such disorders does carry promise, but is fraught with challenges and difficulties. This study was conducted to assess the utility of genetic testing in a cohort of 200 patients who had neurological disorders, suspected to be of inherited origin, and for whom molecular genetic testing was requested during the period 2014 to 2019. Two hundred and eight tests were ordered. The characteristics of that practice were reviewed. Further, we summarized the challenges and highlighted the concerns that were raised. The medical records of 200 patients were retrieved and reviewed to assess the demographic characteristics of the cohort, their clinical presentation, genetic test requested for each, and the interpretation of the test results.
Keywords: genetic; neurology; Iraq